Design and characterisation of piperazine-benzofuran integrated dinitrobenzenesulfonamide as Mycobacterium tuberculosis H37Rv strain inhibitors - Vallabhaneni S. Murthy; Yasinalli Tamboli; Vagolu Siva Krishna; Dharmarajan Sriram; Siddique Akber Ansari; Abdullah A. Alarfaj; Abdurahman H. Hirad; Vijayaparthasarathi Vijayakumar (Taylor & Francis Group, 2021)
Molecular hybridisation of four bioactive fragments piperazine, substituted-benzofuran, amino acids, and 2,4-dinitrobenzenesulfonamide as single molecular architecture was designed. A series of new hybrids were synthesised and subjected to evaluation for their inhibitory activity against Mycobacterium tuberculosis (Mtb) H37Rv. 4d-f and 4o found to exhibit MIC as 1.56 µg/mL, equally active as ethambutol whereas 4a, 4c, 4j displayed MIC 0.78 µg/mL were superior to ethambutol. Tested compounds demonstrated an excellent safety profile with very low toxicity, good selectivity index, and antioxidant properties. All the newly synthesised compounds were thoroughly characterised by analytical methods. The result was further supported by molecular modelling studies on the crystal structure of Mycobacterium tuberculosis enoyl reductase.